Synthesis of polynitrostilbenes using activated hydrotalcites as heterogeneous base catalysts. (1st October 2014) - Xu, Junhui; Wei, Jianping; Ma, Qingguo; Peng, Xinhua
An efficient and straightforward synthesis of polynitrostilbenes with the (E)-configuration by the condensation of polynitroarenes with aromatic aldehydes, catalysed by activated hydrotalcites as heterogeneous catalysts is described.